(3MGdI GdJdHS ai VhA GdSjGSI GdbVGFjI (B/s - (3gfO THjH GdVeQGfi YHO GdQMefs; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3Ef JdGbj GdELQGAGJ GdLfGFjI HacQI Mbhb GdEfSGf djS HGdCeQ GdeSJZQH, Pdc Cf GdgOa GdCSej deG fSejg HGdELQGAGJ GdLfGFjI gh UjGfI LedI GdMbhb GdJi JYJQa HgG GdbhGfjf GdhWfjI h GdehGKjb GdOhdjI ddEfSGf ef MjK chfg EfSGfkG(B. (3aefP Cf MQe GdCaQGO SdWI EbGeI bVGA NGU, h MQe GdeLfi Ydjg ef Mbg aj GdEfJbGe GdaQOi, CNPJ GdOhdI Ydi YGJbgG GdGdJRGe HEbGeI GdYOGdI ai GdeLJeY h MSf JhRjYgG Ydi GdehGWfjf,hGdMb Cf GdJdGbi Hjf GdELQGAGJ GdLfGFjI cCMO COhGJ OhdI GdbGfhf h Hjf Mbhb GdEfSGf bO jNda hLg ef ChLg GdJUGOe Ch GdJYGQV, HMSHGf Cf Ld GdELQGAGJ GdLfGFjI bO JYWd eeGQSI GdMbhb GdCSGSjI ddaQO HZjI GdMaGX Ydi cjGf GdeLJeY hJhbjg NWQ GdLQjeI(B. (3aGdbHV h GdMHS GdGMJjGWi, hGdJaJjT, h GdJMaX Ydi GdCTjGA h VHWgG, h cPG eQGbHI GdeQGSdGJ h GdGJUGdGJ GdJdjahfjI, LejYgG ELQGAGJ JeS HWGFaI ef GdMbhb GdeSJbQI ddEfSGf, cMbg ai GdJfbd, h Mbg ai GdedcjI, h Mbg aj GdMjGI GdNGUI(B.... (3GdN aYfUQ GdOaGY Yf MQjI GdaQO jba eJYGQVkG, efP HOA GdELQGAGJ GdLfGFjI, eY Mb GdeLJeY ai edGMbI GdeLQejf ddfjd efgs
The convergence of criminal procedures with the idea of human rights is not surprising, because the ultimate goal of what we call criminal procedures is to preserve the totality of rights recognized by national laws and international charters for a person as a human being. Since individuals have been deprived of the authority to establish a special judiciary, and the victim has been deprived of his right to individual revenge, the state has taken upon itself the obligation to establish justice in society and to properly distribute it to citizens. Collision or conflict, given that most criminal procedures impede the exercise of the basic rights of the individual in order to preserve the integrity of society and prevent the risk of crime. Arrest, pretrial detention, searches, seizing and seizing things, as well as monitoring correspondence and telephone communications, are all measures that affect a range of human rights, such as the right to movement, the right to property, the right to a private life....etc. The element of defending the freedom of the individual stands in conflict. , since the start of criminal procedures, with the right of society to pursue criminals to undermine it.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2022.s
(3HHdjhLQGajG(B: (3UaMGJ(B. 128-133.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJdHSs; (3GdJaJjTs; (3GdbHVs; (3GdMHS GdGMJjGWjs; (3VeGfGJ GdeJge aj MGdI GdJdHSs; (3HWdGf GdJaJjTs; (3JaJjT GdCfKis; (3GdJdHSs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2022